The Correlation between Fasting Blood Glucose Level with Infiltrated Axillary Limph Node Rate in Infiltrating Ductal Carcinoma of the Breast - Thomas Aribowo; Widyanti Soewoto (Universitas Kristen Maranatha, 2017)
Cancer cell have been shown to extensively use glucose for proliferation, even at hypoxia environment. The consumption of glucose in a hypoxia environment induced HIF and VEGF, which play a role in cancer cell infiltration process . The objective of study is to determine the relationship between fasting blood glucose levels with the amount of infiltrated axillary lymph node in patients with infiltrating ductal carcinoma. This is an analytic observational study with cross sectional design. The data obtained were tested with chi-square test (Î± < 0.05). This study was conducted on 24 infiltrating ductal carcinoma patients. The results showed p value of 0.004, indicating there is a significant correlation between fasting blood glucose levels with the amount of infiltrated axillary lymph nodes. The correlation coefficient ( r) value was 0.505; indicating medium level correlation. As conclusion, there is a significant correlation between fasting blood glucose levels with the amount of infiltrated axillary lymph node in patients with infiltrating ductal carcinoma.Keywords: axillary lymph nodes, breast cancer, fasting blood glucose level, infiltrating ductal carcinoma